2014
DOI: 10.1021/je500440y
|View full text |Cite
|
Sign up to set email alerts
|

Use of G4 Theory for the Assessment of Inaccuracies in Experimental Enthalpies of Formation of Aliphatic Nitro Compounds and Nitramines

Abstract: The gas-phase enthalpies of formation (Δ f H 298 o ) of 57 aliphatic nitro compounds and nitramines (mono-and polynitro compounds including cyclic compounds and well-known explosives such as hexogen, octogen, and CL-20) were calculated using the Gaussian-4 (G4) theory applied to the atomization and isodesmic reaction energies. The Δ f H 298 o (g) values calculated from the atomization reactions were underestimated by an average of 10 kJ·mol −1 , and they could not be used for the assessment of inaccuracies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 73 publications
9
40
0
Order By: Relevance
“…Figure 3 shows that the G4 calculation applied to atomization reaction overestimates the enthalpy of formation of guanidine; the addition of one or two NH 2 groups has a small influence on the D f H 298 (g) value, while that of three amino groups increases the overestimation effect. Earlier it was found that G4 theory underestimates the D f H 298 (g) values for nitro compounds [22,23]. The same trend, as can be seen from Fig.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Figure 3 shows that the G4 calculation applied to atomization reaction overestimates the enthalpy of formation of guanidine; the addition of one or two NH 2 groups has a small influence on the D f H 298 (g) value, while that of three amino groups increases the overestimation effect. Earlier it was found that G4 theory underestimates the D f H 298 (g) values for nitro compounds [22,23]. The same trend, as can be seen from Fig.…”
Section: Resultssupporting
confidence: 82%
“…The same trend, as can be seen from Fig. 3, is also observed for nitroguanidines; however, the presence of guanidine fragment decreases this underestimation somewhat compared to aliphatic and aromatic nitro compounds [22,23]. The largest underestimation is observed for dinitroguanidines; the addition of NH 2 groups somewhat compensates for the effect of NO 2 groups.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations